A stacked Al/Ag anode for short circuit protection in ITO free top-emitting organic light-emitting diodes. Issue 117 (11th November 2015) - Qian, Min; Shi, Xiao-Bo; Ma, Jie; Liang, Jian; Liu, Yuan; Wang, Zhao-Kui; Liao, Liang-Sheng
Abstract : The stacked Al/Ag in place of a Ag anode solves the severe short circuit issues in TEOLED on normal glass substrates. Abstract : Aluminum and silver (Al/Ag) stacked films are utilized as the anode in ITO free top-emitting organic light-emitting devices (TEOLEDs). Serious short circuit issues can be resolved since the stacked metal films can increase the crystallinity and smoothen the surface morphology to suppress the poor infiltration between pure Ag and glass substrates. Optical simulations are carried out based on a transfer matrix method and microcavity effect to guide the real fabrications of the fluorescent TEOLEDs. The stacked Al (56 nm)/Ag (44 nm) anode based TEOLEDs demonstrate a better device performance than that of the Al-only anode based devices. The proposed stacked metal electrode provides a simple and convenient way to fabricate TEOLEDs with suppressed electrical short circuits.